2019
DOI: 10.1080/10643389.2019.1672510
|View full text |Cite
|
Sign up to set email alerts
|

Breakthroughs in the fabrication of electrospun-nanofiber-supported thin film composite/nanocomposite membranes for the forward osmosis process: A review

Abstract: Research on membrane technology to provide fresh water while considering inextricably linked energy issues has resulted in remarkable accomplishments in the production of membranes, such as thin film composite (TFC) membranes, for relatively lowenergy desalination and wastewater reclamation via the forward osmosis (FO) process. Exhaustive and continuous efforts in the enlargement of TFC membranes to achieve an excellent combination of flux and selectivity have revealed a considerable need to fabricate an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 238 publications
(283 reference statements)
0
19
0
Order By: Relevance
“…Nanofibrous TFC‐FO membranes are however hindered by their low mechanical resistance and a risk of the PA active layer delaminating from its substrate. [ 37 ] SEM images of TFC membranes with various substrate structures are presented in Figure 4. To the best of our knowledge, there are no commercial nanofibrous TFC‐FO membranes available.…”
Section: Database and Comparison Criteria Of The Manufacturing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanofibrous TFC‐FO membranes are however hindered by their low mechanical resistance and a risk of the PA active layer delaminating from its substrate. [ 37 ] SEM images of TFC membranes with various substrate structures are presented in Figure 4. To the best of our knowledge, there are no commercial nanofibrous TFC‐FO membranes available.…”
Section: Database and Comparison Criteria Of The Manufacturing Techniquesmentioning
confidence: 99%
“…The reduction of water flux in FO is fundamentally governed by the ICP phenomenon which is closely linked to the support layer's integral structural parameter. Because of the osmotic pressure gradient across the membrane's active layer, the water in the FS migrates to the support layer where it mixes with the DS which then becomes diluted [ 37,57,58,64,80 ] and exhibit a lower osmotic pressure than the bulk DS. This reduces the osmotic pressure gradient across the active layer, therefore, lowering the water flux across the membrane.…”
Section: Comparison Of Substrate Manufacturing Techniquesmentioning
confidence: 99%
“…Compared to phase inversion, electrospinning is another synthesis technique that has a better control on the tortuosity structure of the membrane [56,57]. Synthesis conditions such as environment conditions, solution viscosity, flow rate of the solution, and the applied voltage can be fine-tuned to obtain the membrane with desirable structural characteristics [34,58]. For example, Song et al ( 2014) adjusted the temperature to control the thickness of nanofibers within 50-150 nm [59].…”
Section: B Electrospinningmentioning
confidence: 99%
“…Electrospun membranes, generally termed nanofibers membranes, show great promise in water treatment applications due to their outstanding features such as high surface area, mechanical robustness, small pores, porosity, and lightweight [37]. Several studies were reported in literature for the application of electrospun nanofibers in MBRs [38,39], MF [40], UF [41], NF [42], RO [43], ED [44], MD [45], membrane contactors [46] and FO [47]. We believe that writing a short review on the applications of electrospun nanofiber membranes in the food industry wastewater treatment is essential to state the current status of the research progress and its future potential suggesting research directions for further developments.…”
Section: Introductionmentioning
confidence: 99%